Association of serum immunoglobulin M and immunoglobulin G antibody levels with different indicators of metabolic syndrome - Manali Sinharay,; Chowdhury, Pritam; Dasgupta, Anindya; Karmakar, Arindam (Asian Journal of Medical Sciences, 2023)
Background: Metabolic syndrome (MS) is an assemblage of biochemical derangements of glucose metabolism, dyslipidemia, hypertension, and central obesity allied with implacable low-grade inflammation. Aims and Objectives: The current cross-sectional study was conducted to evaluate the levels of serum Immunoglobulin IgM, and IgG concentrations in subjects with and without MS. Materials and Methods: The study population included 50 adults with MS as cases confirmed by estimation of serum triglyceride (TG), high-density lipoprotein cholesterol (HDL-C), Fasting Plasma Glucose, waist circumference, and blood pressure. Serum IgM and IgG levels were evaluated in cases and controls (from a healthy population), followed by statistical analysis, with the significance level set at P<0.05. Results: The comparison of the serum IgM levels between the case and control groups revealed that the level was significantly higher in the former (P<0.001) compared to the latter, but no statistically significant difference existed in the IgG values. Correlation analysis showed significant positive correlation of IgM with TG (ρ=+0.870, P<0.001), waist circumference (ρ=+0.683, P=0.009) and negative correlation with HDL-C (ρ=−0.751, P<0.001). A significant positive correlation of IgG with waist circumference (ρ=+0.889, P<0.001) was derived. Regression analysis affirmed that statistically, TG (R2=0.768), waist circumference (R2=0.751), and HDL-C (R2=0.705) significantly explained the variance in IgM, whereas IgG was related to only waist circumference. Conclusion: The present study provides a novel perspective that IgM may be involved in the pathogenesis of MS in a population from eastern India, and the outcome suggests the association between IgM and MS may be through lipid metabolism disorders and obesity.